CODE-SWITCHING USED BY SACHA STEVENSON IN TALK SHOWS - Faiz, Ahmad (Balai Bahasa Kalimantan Tengah, 2017)
This research investigates the use of types and functions of code-switching used by Sacha Stevenson as a guest star in Tonight Show and Sarah Sechan on NET TV. Tonight Show and Sarah Sechan are two popular talk shows on NET TV. In order to find the type and the function of code-switching used, the writer uses descriptive qualitative approach. The data is in the form of conversation. In order to collect the data, the writer compiles videos based on the sequence and the context of the conversation. The result shows that the types of code-switching found in both sources are intra-sentential code-switching, inter-sentential code-switching and establishing continuity toward previous speaker emblematic or tag-switching. The functions of code-switching found in both data sources are covering the difficulty in speaking Indonesian, reducing or avoiding face and increasing prestige to be viewed as an educated person and covering inability in speaking Indonesian. This research cannot do a direct interview with Sacha Stevenson. Therefore, it can give chance to other researchers to find the reason of using code-switching used by Sacha Stevenson which can be applied by observing and interviewing her immediately